Aluminum alloy surface and treatment method thereof
Through pulse anodizing and sealing treatment technology, the components in the specific electrolyte and sealing liquid are used to form a dense oxide layer and sealing film layer, solving the problem of corrosion and wear on the surface of aluminum alloy, and achieving a more efficient and environmentally friendly surface treatment effect.
Patent Information
- Application Number
- CN202510344750.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-24
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-24
AI Technical Summary
Untreated aluminum alloy surfaces are susceptible to oxidation, wear and corrosion, limiting their performance.
Using pulse anodizing and sealing treatment methods, a porous oxide layer is formed by sulfuric acid, tea polyphenols, cerium nitrate and nanoalumina in the electrolyte, and the oxide layer is filled and repaired by chitosan, nano zinc oxide and cerium complexes in the sealing liquid to form a dense sealing film layer.
It significantly improves the corrosion resistance, wear resistance and coating adhesion of the aluminum alloy surface, while reducing the impact on the environment, forming a more efficient and environmentally friendly surface treatment solution.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum alloy surface treatment, in particular to an aluminum alloy surface and a treatment method thereof. Background Art
[0002] Aluminum alloys are widely used in aerospace, automobile manufacturing, electronic equipment, and architectural decoration due to their lightweight, high strength, and corrosion resistance. However, the untreated aluminum alloy surface is susceptible to oxidation, wear, and corrosion, which limits its performance. Traditional aluminum alloy surface treatment technologies mainly include anodizing, electroplating, spraying, and chemical conversion coatings. Among them, anodizing generates a porous oxide film on the surface of the aluminum alloy through an electrochemical reaction, and then forms a stable protective layer through sealing treatment. Chemical conversion film technology forms a protective film on the surface of the aluminum alloy through a chemical reaction, which improves its corrosion resistance and coating adhesion, and helps the subsequent chemical treatment process of the aluminum alloy surface.
[0003] In recent years, with the development of nanotechnology, nanomaterials have been introduced into the surface treatment of aluminum alloys to further improve their performance. Prior art CN114836805A discloses a method for surface treatment of aluminum alloys, including substrate surface pretreatment, micro-arc oxidation electrolyte configuration, micro-arc oxidation treatment and sealing. Among them, the micro-arc oxidation electrolyte uses a nanomaterial-nanographene. CN105970268A discloses a treatment method for anodizing and sealing the surface of an aluminum alloy. The sealing material of the invention contains nano silicon oxide and adopts two sealing treatments. The present invention discloses a nano aluminum alloy surface treatment process, which can not only effectively improve the corrosion resistance and wear resistance of the aluminum alloy surface, but also enhance the adhesion of the coating, while reducing the impact on the environment in traditional processes. The realization of this technology is expected to bring more efficient and environmentally friendly solutions to the field of aluminum alloy surface treatment. Summary of the invention
[0004] In order to overcome the above technical problems, the present invention provides an aluminum alloy surface and a treatment method thereof. The aluminum alloy surface treatment method of the present invention enables the surface of the aluminum alloy substrate to contain a pulse oxidation layer and a closed film layer, and the formed aluminum alloy surface has good mechanical properties, insulation properties and anti-aging properties.
[0005] The present invention solves the above technical problems through the following technical solutions.
[0006] The present invention discloses a method for treating the surface of an aluminum alloy, comprising the following steps: The surface of the aluminum alloy is cleaned, chemically pretreated, pulse anodized, and then sealed; The electrolyte used in the anodizing process comprises, by mass percentage, 10-30% sulfuric acid, 0.5-1% tea polyphenols, 0.1-0.3% cerium nitrate and 0.2-0.5% nano-aluminum oxide; The sealing liquid used for sealing comprises, by mass percentage, 0.5-1% chitosan particles, 0.2-0.5% nano zinc oxide and 0.1-0.3% cerium complex; Wherein, the cerium complex is cerium oxalate (15750-47-7) or hydrated cerium acetylacetonate (CAS No.: 206996-61-4).
[0007] Preferably, the electrolyte used for the anodizing comprises, by mass percentage, 10-20% sulfuric acid, 0.5-1% tea polyphenols, 0.1-0.3% cerium nitrate and 0.2-0.5% nano-aluminum oxide.
[0008] The sulfuric acid in the electrolyte, as the basis of the electrolyte, provides hydrogen ions and sulfate ions, forms an acidic environment, promotes the occurrence of anodic oxidation reaction, and helps to form a porous Al2O3 oxide layer on the surface of the aluminum alloy. The phenolic hydroxyl groups of tea polyphenols can be adsorbed on the surface of the aluminum alloy. This adsorption can inhibit local corrosion and excessive dissolution, especially in the high current density area, and avoid the uneven growth of the oxide film. In addition, the antioxidant property of tea polyphenols can reduce the occurrence of side reactions in the electrolyte and improve the stability of the electrolyte. The cerium (III) ions in cerium nitrate will be embedded in the alumina lattice during the anodization process to form a rare earth-doped oxide layer. This doping can refine the grain structure of alumina and improve the hardness and density of the oxide layer. At the same time, the embedding of cerium (III) ions can improve the corrosion resistance and self-healing ability of the oxide layer. The adsorption of tea polyphenols helps the cerium (III) ions to be evenly distributed on the surface of the aluminum alloy, thereby enhancing the effect of rare earth doping. Nano-alumina particles are dispersed in the electrolyte and embedded in the pores of the oxide layer during the anodization process. These nanoparticles can fill the micropores in the oxide film and reduce the pore size, thereby improving the density and wear resistance of the oxide layer.
[0009] Preferably, the sealing liquid used for sealing comprises: 0.5-1% chitosan particles, 0.2-0.5% nano zinc oxide and 0.1-0.3% cerium complex.
[0010] Nano zinc oxide in the sealing liquid has antibacterial and anti-ultraviolet properties, and can also fill the micropores of the pulse anodized film, improve the surface density and hardness, and enhance the wear resistance of the sealed film layer. The amino and hydroxyl groups in chitosan molecules have strong adsorption capacity. As a film-forming matrix, they can disperse nano zinc oxide and prevent the agglomeration of nano-scale particles. To a certain extent, they can also improve the density of the sealed film layer through the filling effect with nano zinc oxide. Compared with traditional chromium-containing sealers, chitosan has the advantages of being environmentally friendly and non-toxic. When the cerium complex is exposed to an oxidizing environment (such as oxygen and water) for a long time, the cerium complex releases cerium (III) ions, which migrate to the damaged area. The oxide deposition of cerium (III) ions can actively repair the damaged area and delay corrosion. The chemical reaction between cerium and chitosan can also enhance the stability of the sealed film layer. Therefore, cerium and zinc form a bimetallic protective layer, which can significantly improve the comprehensive performance of the sealed film layer and improve the durability of the coating.
[0011] In some preferred embodiments, the D99 of the chitosan particles is ≤180 μm.
[0012] In some preferred embodiments, the particle size of the nano zinc oxide is 30±10 nm.
[0013] In some preferred embodiments, the purity of the tea polyphenols is ≥98%.
[0014] In some preferred embodiments, the D50 of the nano-aluminum oxide is 10-60 nm, preferably 20-30 nm.
[0015] In some preferred embodiments, the pulse anodizing temperature is 20-45°C, preferably 20-25°C.
[0016] In some preferred embodiments, the pulse anodizing time is 30 to 60 minutes.
[0017] In some preferred embodiments, the frequency of the pulse anodizing is 100-500 Hz, preferably 300-500 Hz.
[0018] In some preferred embodiments, the duty cycle of the pulse anodization is 40-50%.
[0019] In some preferred embodiments, the sealing treatment is performed by immersion.
[0020] In some preferred embodiments, the sealing treatment temperature is 50-60°C.
[0021] In some preferred embodiments, the sealing treatment time is 20 to 30 minutes.
[0022] In some preferred embodiments, the sealing treatment is performed with the assistance of ultrasound at a frequency of 15 to 40 kHz; preferably, the sealing treatment is performed with the assistance of ultrasound at a frequency of 20 to 40 kHz.
[0023] In some preferred embodiments, the chemical pretreatment is performed by soaking in a zirconium-titanium conversion solution for 5 to 10 minutes at a soaking temperature of 50 to 60°C.
[0024] In some preferred embodiments, the zirconium-titanium conversion solution contains 1~3 g / L fluorozirconic acid (H2ZrF6), 0.5~2 g / L fluorotitanic acid (H2TiF6), 1~2 g / L ammonium fluoride (NH4F), 0.5~1 g / L citric acid and 0.1~0.5 g / L surfactant.
[0025] In some preferred embodiments, the cleaning includes degreasing and pickling.
[0026] In some preferred embodiments, water washing is required after the degreasing and the pickling.
[0027] In some preferred embodiments, the degreasing temperature is 60-70° C., and the degreasing time is 180-300 s.
[0028] In some preferred embodiments, the degreasing agent used in the degreasing comprises 10-20 g / L sodium hydroxide, 10-20 g / L trisodium phosphate, 20-30 g / L sodium carbonate and 1-3 g / L surfactant.
[0029] In some preferred embodiments, the pickling temperature is 15-30° C., and the pickling time is 60-120 s.
[0030] In some preferred embodiments, the pickling agent used in the pickling includes, by mass fraction, 30-50 g / L concentrated sulfuric acid (98% concentrated sulfuric acid), 3-8 g / L ammonium bifluoride, 2-4 g / L citric acid, 1-3 g / L sodium nitrate, 0.5-1 g / L ferric sulfate and 1-2 g / L dipropylene glycol.
[0031] The invention also discloses an aluminum alloy surface, which is obtained by the above-mentioned aluminum alloy surface treatment method.
[0032] The aluminum alloy surface includes an aluminum alloy substrate, an anodized layer and a closed film layer.
[0033] The thickness of the pulse anodized film layer is 5-15 μm, preferably 5-11 μm; the pulse anodized film layer is a film layer formed after the pulse anodizing.
[0034] The thickness of the sealing film layer is 0.3-1.0 μm, preferably 0.3-0.8 μm; the sealing film layer is a film layer formed after sealing treatment.
[0035] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0036] Compared with the prior art, the present invention has the following beneficial effects: 1. In the pulse anodizing process of the present invention, tea polyphenols inhibit corrosion and side reactions through adsorption, while helping the cerium (III) ions to be evenly distributed; the cerium (III) ions in cerium nitrate are embedded in the alumina lattice, refining the grains, enhancing hardness, density and corrosion resistance; nano alumina particles fill micropores, further improving density and wear resistance. These components work synergistically to optimize the performance of the pulse anodized film layer.
[0037] 2. In the sealing liquid, nano zinc oxide can fill the micropores of the pulse anodized film due to its antibacterial and UV resistance, improve the surface density and hardness, and enhance wear resistance. Chitosan has strong amino and hydroxyl adsorption capacity, and can be used as a film-forming matrix to disperse nano zinc oxide, prevent agglomeration, and improve the density of the closed film layer. It is also environmentally friendly and non-toxic. The cerium complex releases cerium (III) ions in an oxidizing environment, migrates to the damaged area and deposits oxides to repair damage and delay corrosion. At the same time, the chemical reaction between cerium and chitosan further enhances the stability of the film layer. Finally, the bimetallic protective layer formed by cerium and zinc significantly improves the comprehensive performance and durability of the closed film layer.
[0038] 3. The aluminum alloy surface treatment of the present invention also includes cleaning and chemical pretreatment processes. The degreasing process can remove grease, oil stains and other organic matter on the aluminum alloy surface to prevent these substances from forming an isolation layer in the subsequent treatment process and hindering the chemical reaction; the chemical pretreatment is that after being immersed in the zirconium-titanium conversion liquid, a zirconium-titanium conversion film will be formed on the aluminum alloy surface. This conversion film can improve the corrosion resistance of the aluminum alloy surface and enhance the adhesion and uniformity of the subsequent anodized film.
[0039] 4. The present invention forms a pulse anodized film layer and a closed film layer on the surface of the aluminum alloy through pulse anodizing and sealing treatment. The pulse anodized film layer has good corrosion resistance and wear resistance, and the aluminum alloy surface also has good toughness and can effectively resist external mechanical impact. The closed film layer further enhances the corrosion resistance and wear resistance of the aluminum alloy surface. In addition, the nano zinc oxide in the closed film layer gives the surface antibacterial and anti-ultraviolet aging capabilities, while the cerium complex has self-healing ability and can maintain good protective performance during long-term use. The closed film layer of the present invention eliminates the use of traditional chromium-containing sealants and instead uses chitosan, a natural material, to make the entire treatment process more environmentally friendly. DETAILED DESCRIPTION
[0040] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and carefully in combination with preferred embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments.
[0041] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0042] The "range" disclosed in the present invention is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of end values, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60-120 and 80-110 is listed for a specific parameter, it is understood that the range of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" represents that all real numbers between "0-5" have been fully listed herein, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0043] If not otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form a new technical solution.
[0044] Unless otherwise specified, all technical features and optional technical features of the present invention can be combined with each other to form a new technical solution.
[0045] If not otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0046] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0047] If not specifically stated, in the present invention, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0048] The thickness of the anodized film layer and the thickness of the sealing film layer on the surface of the aluminum alloy in the following examples and comparative examples are tested by a beam microscope method, with specific reference to GB / T 8014.3.
[0049] The deacetylation degree of chitosan particles is ≥85%, D99=177~180μm.
[0050] Nano zinc oxide was purchased from Shanghai Dingfen Chemical Technology Co., Ltd. with a particle size of 30 ± 10 nm.
[0051] Tea polyphenols were purchased from Nanjing Dosfu Biotechnology Co., Ltd. with a purity of >98%.
[0052] Nano-alumina was purchased from Bohuasi Nano-Tech (Ningbo) Co., Ltd., and the D50 of nano-alumina was 20 nm.
[0053] Example 1 The treatment method of the aluminum alloy surface of this embodiment is as follows:
[0054] (1) Cleaning: Cleaning the aluminum alloy surface, i.e., degreasing, water washing, pickling and water washing in sequence; Degreasing at 60℃ for 220s, then washing twice at 20℃, each washing time is 30s; pickling at 20℃ for 110s, then washing twice at 20℃, each washing time is 30s; degreasing and pickling are both done by immersion; The degreasing agent used for degreasing is composed of 20 g / L sodium hydroxide, 14 g / L trisodium phosphate, 21 g / L sodium carbonate and 2.7 g / L surfactant (sodium dodecyl sulfate), and the solvent is water; The pickling agent used for pickling is composed of 45g / L concentrated sulfuric acid (concentration 98%), 6g / L ammonium bifluoride, 3.5g / L citric acid, 2.8g / L sodium nitrate, 0.7g / L ferric sulfate and 1.2g / L dipropylene glycol (CAS No.: 25265-71-8), and the solvent is water; (2) Chemical pretreatment: The aluminum alloy surface cleaned in step (1) is immersed in a zirconium-titanium conversion solution for 8 minutes at a temperature of 60° C.; The zirconium-titanium conversion solution contains 2 g / L fluorozirconic acid, 0.8 g / L fluorotitanic acid, 1.5 g / L ammonium fluoride, 0.6 g / L citric acid and 0.3 g / L sodium dodecyl sulfate (surfactant).
[0055] (3) Pulse anodizing: The aluminum alloy surface after chemical pretreatment in step (2) was pulse anodized at 25°C for 50 minutes, with a pulse frequency of 500 Hz and a pulse duty cycle of 50%; after pulse anodization, it was washed with water at 20°C for 40 seconds, twice; Calculated by mass percentage, the electrolyte composition is 15% sulfuric acid, 0.6% tea polyphenols, 0.3% cerium nitrate and 0.35% nano-alumina, and the solvent is water.
[0056] (4) Closure treatment: The aluminum alloy surface after pulse anodization in step (3) is sealed at 50° C. for 25 min, using 30 kHz frequency ultrasonic assistance; after the sealing treatment, it is washed with water at 20° C. for 40 s, twice; The sealing solution consists of 0.8% chitosan particles, 0.45% nano zinc oxide and 0.15% cerium complex (hydrated cerium acetylacetonate).
[0057] (5) Drying: Dry at 120°C for 25 min.
[0058] The thickness of the pulse anodized film layer in this embodiment is 8 μm; the thickness of the sealing film layer is 0.6 μm.
[0059] Example 2 The difference between this embodiment and embodiment 1 is only that: Pulse anodizing: pulse anodizing for 40 min at 25 °C, with a pulse frequency of 500 Hz and a pulse duty cycle of 40%; Calculated by mass percentage, the electrolyte composition is 10% sulfuric acid, 1.0% tea polyphenols, 0.25% cerium nitrate and 0.5% nano-alumina, and the solvent is water.
[0060] The thickness of the pulse anodized film layer in this embodiment is 5 μm.
[0061] Other steps and parameters are the same as in Example 1.
[0062] Example 3 The difference between this embodiment and embodiment 1 is only that: Sealing treatment: Sealing treatment was carried out at 60°C for 20 min, using 30kHz ultrasound assistance; The sealing solution contains 1.0% chitosan particles, 0.3% nano zinc oxide and 0.3% cerium complex (cerium oxalate) by mass percentage.
[0063] The thickness of the sealing film layer in this embodiment is 0.75 μm.
[0064] Other steps and parameters are the same as in Example 1.
[0065] Example 4 The difference between this embodiment and embodiment 1 is that: The degreasing agent contains 20g / L sodium hydroxide, 10g / L trisodium phosphate, 30g / L sodium carbonate and 2g / L surfactant, and the solvent is water; The pickling agent consists of 50 g / L concentrated sulfuric acid (98% concentration), 5 g / L ammonium bifluoride, 2 g / L citric acid, 1.5 g / L sodium nitrate, 0.5 g / L ferric sulfate and 1.8 g / L dipropylene glycol, and the solvent is water.
[0066] The thickness of the pulse anodized film layer in this embodiment is 9 μm; the thickness of the closed film layer is 0.65 μm.
[0067] Other steps and parameters are the same as in Example 1.
[0068] Example 5 The difference between this embodiment and embodiment 1 is only that: Soak in zirconium-titanium conversion solution for 5 minutes at a temperature of 50°C; The zirconium-titanium conversion solution contains 2.4 g / L fluorozirconic acid, 1.5 g / L fluorotitanic acid, 1.0 g / L ammonium fluoride, 1.0 g / L citric acid and 0.5 g / L surfactant (sodium dodecyl sulfate).
[0069] The thickness of the pulse anodized film layer in this embodiment is 8.4 μm; the thickness of the closed film layer is 0.61 μm.
[0070] Other steps and parameters are the same as in Example 1.
[0071] Comparative Example 1 The difference between this comparative example and Example 1 is: Calculated by mass percentage, the electrolyte composition is 15% sulfuric acid, 0.3% cerium nitrate and 0.5% nano-alumina, and the solvent is water.
[0072] The thickness of the pulse anodized film layer in this comparative example is 7.1 μm.
[0073] Other steps and parameters are the same as in Example 1.
[0074] Comparative Example 2 The difference between this comparative example and Example 1 is: Calculated by mass percentage, the electrolyte composition is 15% sulfuric acid, 0.6% tea polyphenols and 0.3% cerium nitrate, and the solvent is water.
[0075] The thickness of the pulse anodized film layer in this comparative example is 7.4 μm.
[0076] Other steps and parameters are the same as in Example 1.
[0077] Comparative Example 3 The difference between this comparative example and Example 1 is: Calculated by mass percentage, the electrolyte components include: 15% sulfuric acid, 0.15% tea polyphenols, 0.3% cerium nitrate, 0.6% nano-alumina, and the solvent is water.
[0078] The thickness of the pulse anodized film layer in this comparative example is 7.8 μm.
[0079] Other steps and parameters are the same as in Example 1.
[0080] Comparative Example 4 The difference between this comparative example and Example 1 is: Calculated by mass percentage, the sealing solution contains 0.5% nano zinc oxide and 0.2% cerium complex.
[0081] The thickness of the sealing film layer of this comparative example is 0.47 μm.
[0082] Other steps and parameters are the same as in Example 1.
[0083] Comparative Example 5 The difference between this comparative example and Example 1 is:
[0084] The sealing liquid contains 2% chitosan particles, 0.5% nano zinc oxide and 0.3% cerium complex in terms of mass percentage.
[0085] The thickness of the sealing film layer in this comparative example is 0.77 μm.
[0086] Other steps and parameters are the same as in Example 1.
[0087] Comparative Example 6 The difference between this comparative example and Example 1 is: This comparative example does not include the step of (2) chemical pretreatment.
[0088] The thickness of the pulse anodized film layer in this comparative example is 7.2 μm, and the thickness of the sealing film layer is 0.56 μm.
[0089] Other steps and parameters are the same as in Example 1.
[0090] Test Case The insulation, wear resistance and light and heat resistance properties of the aluminum alloy surfaces of the above-mentioned embodiments and comparative examples were tested. The test results are shown in Table 1.
[0091] The insulation test is carried out at a temperature of 23℃±2℃ and a relative humidity of ≤65%. The specific test method refers to GB / T 8754.
[0092] The wear resistance test was conducted three times with a load of 19.6N and 240-mesh silicon carbide sandpaper, and the average value was taken as the final result. The unit of wear rate is one time (double stroke) / 5μm. For details, please refer to GB / T 12967.2.
[0093] The light and heat resistance test is carried out in a constant temperature and humidity chamber at a temperature of 47℃±1℃ and a relative humidity of 96%±2%, using a 313B fluorescent ultraviolet lamp for 800 hours. The specific method refers to GB / T 12967.4. Whether the aluminum alloy surface changes in color, gloss, cracks or peeling occurs, the judgment level standard refers to GB / T 1766.
[0094] Among them, the aluminum alloy in the blank group is an aluminum alloy that has only been cleaned and has not undergone chemical pretreatment, pulse anodizing and sealing treatment processes.
[0095] .
[0096] In Comparative Example 1, the electrolyte does not contain tea polyphenols, and the hardness and density of the pulse anodized film layer formed are reduced. In Comparative Example 2, the electrolyte does not contain nano-alumina, the porosity of the pulse anodized film layer increases, and the wear resistance and hardness are reduced. In Comparative Example 3, the electrolyte contains too much tea polyphenols, and the excessive tea polyphenols will form too much organic matter deposition on the surface of the oxide film, which will not only increase the conductivity of the film layer, but also reduce its wear resistance.
[0097] In comparative example 4, the sealing liquid does not contain chitosan, which leads to a slight decrease in the adhesion of the coating, and the nano zinc oxide particles are easy to agglomerate, thereby weakening the protection of the sealing film layer against ultraviolet rays. In comparative example 5, the chitosan content in the sealing liquid is too high, and too much chitosan will reduce the mechanical properties of the sealing film layer and increase its brittleness.
[0098] In Comparative Example 6, due to the lack of chemical pretreatment, the bonding degree between the cleaned aluminum alloy and the pulse anodized film layer is low, and severe wear and large-scale shedding will occur on the surface of the aluminum alloy during the wear resistance test.
[0099] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods. The specific embodiments described above further describe the purpose, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for treating the surface of an aluminum alloy, characterized in that: The following steps are involved: The surface of the aluminum alloy is cleaned, chemically pretreated, pulse anodized, and then sealed; The electrolyte used in the anodizing process comprises, by mass percentage, 10-30% sulfuric acid, 0.5-1% tea polyphenols, 0.1-0.3% cerium nitrate and 0.2-0.5% nano-aluminum oxide; The sealing liquid used for sealing comprises, by mass percentage, 0.5-1% chitosan particles, 0.2-0.5% nano zinc oxide and 0.1-0.3% cerium complex; Wherein, the cerium complex is cerium oxalate or hydrated cerium acetylacetonate.
2. The method for treating the surface of an aluminum alloy according to claim 1, characterized in that: Meet at least one of the following conditions ①~③: ① The D99 of the chitosan particles is ≤180 μm; ② The particle size of the nano zinc oxide is 30±10nm; ③ The D50 of the nano-alumina is 10~60nm.
3. The method for treating the surface of an aluminum alloy according to claim 1, characterized in that: Meet at least one of the following conditions ①~④: ① The temperature of the pulse anodizing is 20~45°C; ② The pulse anodizing time is 30 to 60 minutes; ③ The frequency of the pulse anodizing is 100~500Hz; ④ The duty cycle of the pulse anodizing is 40-50%.
4. The method for treating the surface of an aluminum alloy according to claim 1, characterized in that: Meet at least one of the following conditions ①~④: ① The sealing treatment method is immersion; ② The temperature of the sealing treatment is 50~60℃; ③ The sealing treatment time is 20 to 30 minutes; ④ The sealing treatment is carried out with the assistance of ultrasound at a frequency of 15~40kHz.
5. The method for treating the surface of an aluminum alloy according to claim 1, characterized in that: The chemical pretreatment method is to soak in a zirconium-titanium conversion solution for 5-10 minutes at a soaking temperature of 50-60°C; The zirconium-titanium conversion solution contains 1-3 g / L fluorozirconic acid, 0.5-2 g / L fluorotitanic acid, 1-2 g / L ammonium fluoride, 0.5-1 g / L citric acid and 0.1-0.5 g / L surfactant.
6. The method for treating the surface of an aluminum alloy according to claim 1, characterized in that: The cleaning includes degreasing and pickling; After the degreasing and pickling, water washing is required.
7. The method for treating the surface of an aluminum alloy according to claim 6, characterized in that: Meet at least one of the following conditions ①~②: ① The degreasing temperature is 60-70°C and the degreasing time is 180-300s; ② The degreasing agent used in the degreasing comprises 10-20 g / L sodium hydroxide, 10-20 g / L trisodium phosphate, 20-30 g / L sodium carbonate and 1-3 g / L surfactant.
8. The method for treating the surface of an aluminum alloy according to claim 6, characterized in that: Meet at least one of the following conditions ①~②: ① The pickling temperature is 15-30°C and the pickling time is 60-120s; ② Calculated by mass fraction, the pickling agent used in the pickling includes 30~50g / L concentrated sulfuric acid, 3~8g / L ammonium bifluoride, 2~4g / L citric acid, 1~3g / L sodium nitrate, 0.5~1g / L ferric sulfate and 1~2g / L dipropylene glycol.
9. Aluminum alloy surface, characterized in that The aluminum alloy surface is obtained by the aluminum alloy surface treatment method as described in any one of claims 1 to 8.
10. The aluminum alloy surface according to claim 9, characterized in that It includes an aluminum alloy substrate, a pulse anodized layer and a sealing film layer; The thickness of the pulse anodized film is 5~15μm; The thickness of the sealing film layer is 0.3-1.0 μm.
Citation Information
Patent Citations
Aluminum alloy surface treatment method
CN114836805A
Antibacterial composite surface and processing method for forming antibacterial composite surface
CN105714352A
Treatment method for aluminum alloy surface anodic oxidation-hole sealing
CN105970268A
Preparation method of high-temperature-resistant corrosion-resistant anodic oxide film
CN110777415A
Process for production of nanocrystallite-containing metal oxide layers on sealing layer forming metals, especially for production of Ti oxide layers useful in catalysis, especially photocatalysis,
DE102005043865A1
Cited By
Self-healing sealing coating concentrated solution as well as preparation method and application thereof
CN120758947A
Self-healing sealing coating concentrate, method for its production and use
CN120758947B